Development of new cross intermolecular pair potential ab initio and prediction of cross second virial coefficients for dimer H2O-CH4 - Tat, Pham Van (Vietnam Journal of Chemistry, 2014)
The site-site intermolecular pair potential of dimer H2O-CH4 was constructed from the ab initio calculations at high level of theory CCSD(T) with basis set cc-pVTZ. The cross second virial coefficients of this system were calculated accurately using this ab initio pair potential. These results were compared with experimental data and those from literatures. The discrepancies between them are insignificant. Keywords: cross intermolecular pair potential, cross second virial, ab initio potential.